Anti-dumping in New Zealand: A century of protection from "unfair" trade? - Martin Garcia; Astrid Baker (New Zealand Institute of Economic Research (NZIER), 2005)
Political pressures and concerns about 'unfair' trade provide the main rationale for retaining broad anti-dumping provisions in most countries. Almost one hundred years ago, New Zealand was the second country in the world to introduce anti-dumping legislation. Since then New Zealand's anti-dumping policy and legislation have changed significantly in response to both internal and external pressures. The key issues over the years have remained essentially the same. To what extent should domestic producers be protected from the effects of dumping? To what extent should the interests of other groups, such as consumers and downstream industries, be taken into account? There is a natural tension between the first issue - protection of the private interests of producers - and the second - the public or national interest. The issues of protectionism and the public interest are at the centre of the debate about anti-dumping. The political factors influencing anti-dumping policy are this study's main focus. The study examines the history of anti-dumping policy in New Zealand, how and why it has been justified and what has shaped it. The study shows that the anti-dumping debate involves the concentrated and organised interests of import-competing industries and their employees, who benefit directly from the protection provided by anti-dumping duties, and other interest groups who bear the more or less widespread costs of anti-dumping action, such as consumers and downstream industries. Manufacturing industries have been able to place significant pressure on governments to retain strong anti-dumping provisions, particularly as other general forms of protection have been removed or reduced and New Zealand has entered into bilateral free trade agreements. Despite this pressure, governments and officials have remained intent on ensuring that anti-dumping does not replace general protection and anti-dumping on trans-Tasman trade was removed in the interests of competition. Recent proposals that competition and wider interests should be considered before taking anti-dumping action have met strong resistance from manufacturers, with pressure from importers, consumers and downstream industries remaining either limited or absent.
Keywords: 330; Antidumping; Protektionismus; Neuseeland